Lateral pallidotomy exacerbates akinesia in the Parkinsonian patient. - Munro-Davies, L; Gregory, R; Squires, W; Radatz, M; Silburn, P; Scott, R; Aziz, T; Stein, J (1999)
Despite the recent resurgence of interest in the use of pallidotomy for the treatment of Parkinson's disease, there remains considerable debate about the optimal lesion site. Although the current understanding of the neural mechanisms underlying Parkinsonism would suggest that the medial pallidum is the logical site for alleviation of symptoms, some surgeons still advocate lesions in the lateral pallidum. We report the case of such a lesion placement verified pathologically, which resulted in exacerbation of akinesia postoperatively. This demonstrates that accurate targeting in the pallidum is critical to avoid exacerbation of symptoms by lesioning the lateral pallidum.